The multilateral development banks. (Boulder, Colo. : L. Rienner, 1995)
"Examines history, structure, functioning, and development of the Inter-American Development Bank (IDB). Major focus is on evaluating IDB's effectiveness in promoting economic growth, reducing poverty, and improving social (i.e., welfare) indicators"--Handbook of Latin American Studies, v. 57.
v. 1. The African Development Bank / E. Philip English, Harris M. Mule -- v. 2. The Asian Development Bank / Nihal Kappagoda -- v. 3. The Caribbean Development Bank / by Chandra Hardy -- v. 4. Inter-American Development Bank / Diana Tussie -- v. 5. Titans or behemoths? / Roy Culpeper.
Includes bibliographical references and indexes.
Keywords: Asian Development Bank; Caribbean Development Bank; African Development Bank; Inter-American Development Bank; Development banks